2013
DOI: 10.1108/nfs-10-2012-0108
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition knowledge in relation to the eating behaviour and attitudes of Slovenian schoolchildren

Abstract: Purpose – Children's eating habits are influenced by numerous social and individual factors. The present study aimed to evaluate the connection between nutrition knowledge of children and their eating habits as well as their attitudes towards healthy eating habits. Design/methodology/approach – The research study included 630 11-year-old children from 27 randomly selected Slovenian schools. During the research, children attended the sixth grade of the nine-year elementary school and on average were subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 25 publications
1
8
0
4
Order By: Relevance
“…It was also noted that the demographic and behavioural data collected did not differentiate the decision‐making process that resulted in the range of EDS data that were obtained. This indicates that the behaviours exhibited by the sample group are consistently adopted (contrary to research carried out by Larson, Perry, Story, & Neumark‐Sztainer, and Hearty, McCarthy, Kearney, & Gibney, ; Kostanjevec, Jerman, & Koch, ), and does support that variables such as knowledge and attitudes are poorly translated into healthy dietary behaviour (Brown, McIlveen, & Strugnell, ). In contrast to research by Cluskey and Grobe (), the study did reveal that although adolescents do attain the knowledge and skills to make healthy food choices, translating this into dietary behaviour does not always occur.…”
Section: Discussionmentioning
confidence: 69%
“…It was also noted that the demographic and behavioural data collected did not differentiate the decision‐making process that resulted in the range of EDS data that were obtained. This indicates that the behaviours exhibited by the sample group are consistently adopted (contrary to research carried out by Larson, Perry, Story, & Neumark‐Sztainer, and Hearty, McCarthy, Kearney, & Gibney, ; Kostanjevec, Jerman, & Koch, ), and does support that variables such as knowledge and attitudes are poorly translated into healthy dietary behaviour (Brown, McIlveen, & Strugnell, ). In contrast to research by Cluskey and Grobe (), the study did reveal that although adolescents do attain the knowledge and skills to make healthy food choices, translating this into dietary behaviour does not always occur.…”
Section: Discussionmentioning
confidence: 69%
“…8,14 Contrary to the results of the present study, previous research has shown that increasing knowledge about nutrition is not enough to affect a change in eating habits. 36 Insufficient knowledge about nutrition is an important cause of poor eating habits, 37 but it is difficult to improve eating habits by increasing nutrition knowledge alone. 36 Recognizing that you are obese is a prerequisite for consciously improving obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown nutritional knowledge as a factor that influence the decisions individuals make about food [20,24,25]. Lack of nutrition knowledge has been implicated as a cause of poor dietary habits [26]. However, knowledge alone may not be adequate to have proper dietary practices.…”
Section: Discussionmentioning
confidence: 99%